A phraseologism-heading as a manipulative dominant of a mediatext - Syzonov, Dmytro (Current issues of Ukrainian linguistics: theory and practice, 2020)
The article* deals with different types of headings with a phraseological component, which is motivated by the manipulative function of media. Thus, journalists resort to manipulation in media when they want to: (a) obscure factual information; (b) affect the mass consciousness of the Ukrainians; (c) focus on key positions of a media text. A phraseologism (as a certain verbal code of mass communication that is characterized by semantic indivisibility, integrity, emotionality and expressiveness) is used primarily to attract the attention of the recipient and to accentuate the main positions of a media text. The role of a phraseologism in the heading of a media text is very high: it is able to succinctly convey the meaning of the main text, motivate the recipient to perceive the material, be apt in the role of media nomination of the phenomenon described. In the context of information competitiveness, the chosen phraseologism-heading helps the media text to be noticed and read by the potential recipient. An attempt is made to classify phraseologisms-headings as the dominant of modern media texts by several criteria (structure, functions and genre affiliation). Such classification was made possible by the broad illustrative material: Ukrainian printed and electronic media, radio and television, advertising, the Internet (2019 – early 2020). Emphasis is made on the correction of the proposed classification due to the expansion of information space and the emergence of new genres with headings of new types. It is proved that a phraseologism-heading in media is used for: attracting the attention of the recipient, focusing on key information, clarifying on some facts, activating the background knowledge of the recipient, pre-comprehension and understanding the text, influencing the mass consciousness. The key goal of a phraseologism-heading remains manipulation. A phraseologism-heading is increasingly used by journalists in modern media communication.  * The article has been prepared within the scope of the scientific project "Ecolinguistic Modes of Discursive Space of Ukraine in the European Multicultural Continuum" (registration number 2020.02/0241) with the support of the National Research Foundation of Ukraine
Keywords: media phraseologism, а phraseologism-heading, Ukrainian media text, media manipulation, media linguistics. *